Karakteristik “Hyperpersonal Communication” dalam “Internet Relay Chat” sebagai Bagian dari “Computer Mediated Comunication” - Anne Maryani (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Computer-mediated-communication (CMC) probably has become the hottest buzzword in the field of media communication nowadays. CMC has laid the basics of hypersonal communication which interrelating agents and subjects of communication process by virtual communication. Internet Relay Chat, as one of CMC product widely used by public, characterizes hypersonal communication which involved sender-receiver interactions, the channel, and the feedback in a new transmitting mode. Emoticon, digital-based-message, and virtual setting set up the nature of sender and receiver. Moreover, it creates a new landscape of communication and generates new functions of communication media.